2009
DOI: 10.1095/biolreprod.108.068882
|View full text |Cite
|
Sign up to set email alerts
|

Sorbitol Can Fuel Mouse Sperm Motility and Protein Tyrosine Phosphorylation via Sorbitol Dehydrogenase1

Abstract: Energy sources that can be metabolized to yield ATP are essential for normal sperm functions such as motility. Two major monosaccharides, sorbitol and fructose, are present in semen. Furthermore, sorbitol dehydrogenase (SORD) can convert sorbitol to fructose, which can then be metabolized via the glycolytic pathway in sperm to make ATP. Here we characterize Sord mRNA and SORD expression during mouse spermatogenesis and examine the ability of sorbitol to support epididymal sperm motility and tyrosine phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…Typical protein modifications during epididymal sperm maturation include tyrosine phosphorylation and serine/threonine phosphorylation [4851]. Interestingly, many phosphatase are also enriched in CDs, such as PPP1CC, PRSS21 and PRSS52, which are all involved in protein serine/threonine phosphorylation, and SORD, a protease associated with protein tyrosine phosphorylation [5254], was also highly enriched in CDs. Thus, CDs also appear to provide modifying enzymes for sperm protein modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Typical protein modifications during epididymal sperm maturation include tyrosine phosphorylation and serine/threonine phosphorylation [4851]. Interestingly, many phosphatase are also enriched in CDs, such as PPP1CC, PRSS21 and PRSS52, which are all involved in protein serine/threonine phosphorylation, and SORD, a protease associated with protein tyrosine phosphorylation [5254], was also highly enriched in CDs. Thus, CDs also appear to provide modifying enzymes for sperm protein modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the activity of sperm SORD, the second enzyme of the polyol pathway, is also increased during capacitation (Baker et al 2010) and that sorbitol can also serve as an energy source for sperm motility and protein tyrosine phosphorylation via SORD (Cao et al 2009). However, under the present experimental conditions, the SORD inhibitor, CP-470,711, did not show any significant effects on the induction of hyperactivated motility.…”
Section: Role Of Aldose Reductase In Sperm Capacitationmentioning
confidence: 99%
“…The biochemical modifications of spermatozoa during capacitation include modulation of enzyme activities, membrane modifications and protein tyrosine phosphorylation (De Jonge 2005). These tyrosine phosphorylation modifications are only partially known at the molecular level, but require an adequate supply of sufficient energy sources (Mukai & Okuno 2004, Ferramosca & Zara 2014, mainly including fructose (Cao et al 2009) and glucose (Urner & Sakkas 2003), the metabolic products (ATP and NADPH) of which appear to participate in signaling pathways by supporting the precise onset of protein tyrosine phosphorylation in the sperm flagellum leading to successful fertilization. The polyol pathway is related to epididymosomes that modulate sperm motility during the epididymal transit, which involves aldose reductase (ALDR) that uses NADPH to reduce glucose to sorbitol.…”
Section: Discussionmentioning
confidence: 99%